SANDEQ DAN ROPPO Kearifan Lokal Suku Mandar Pesisiran, Sulawesi Barat - Kasitowati, Rarasrum Dyah (Fakultas Ilmu Budaya Universitas Diponegoro, 2011)
Mandar tribe is a tribe in the coastal area of West Sulawesi, whose local knowledge is applied to preserve the marine resources through Sandeq boat and roppo fishing equipment. This paper aims to describe Sandeq boat and roppo fishing equipment used by Mandar tribe. The results showed that Sandeq boat and roppo equipment are not only products of local wisdom that can preserve the marine resources, but also have social values that unite people of Mandar tribe.